Pendekatan Public Relations dalam Membangun Opini Publik(Studi Kualitatif di Pesantren Al Mukmin Ngruki Tahun 2011) - Muslimin , Arif (2012)
Islamic Boarding School Al Mukmin Ngruki or commonly referred to as cottage Ngruki, end - the end is a lot of scrutiny from all walks of society as the number of terrorism cases that occur. This cottage is very different from other boarding schools, ranging from the inception of this cottage has been known as one of the huts are in trouble with the government. The problem of terror and terrorism becomes an absolute must, in order to avoid any sense because usually the Muslims who will become victims when reporting about terrorism. Speaking of terrorism we must be careful and as far as possible to avoid prejudice or stereotype, because sometimes it was all done just for the sake of a group of people. Organizations can exist and thrive not because of the confidence of the public, which is the internal strength and external determinants of life - the death of the organization. Public trust to be a major source of strength for any organization with diverse activities, so that good relations with all who have a stake in the company is the key to success for the organization fulfill its mission because it can generate synergies and public confidence. Basically Public Relations aims to gain goodwill, trust and mutual understanding of the public. Have a goal to create public opinion is acceptable and beneficial to all parties, an important element in management is to achieve specific goals according to public expectations. Attempt to create a harmonious relationship between the organization or company and its publics, internally and externally through a reciprocal process while creating public opinion as the effect is very useful as input for the organization or company.